H1N1 influenza virus dose dependent induction of dysregulated innate immune responses and STAT1/3 activation are associated with pulmonary immunopathological damage. Issue 1 (31st December 2022) - Yao, Duoduo; Bao, Linlin; Li, Fengdi; Liu, Bo; Wu, Xu; Hu, Ziqi; Xu, Jiangnan; Wang, Wei; Zhang, Xulong
ABSTRACT: Influenza A virus (IAV) infection poses a substantial challenge and causes high morbidity and mortality. Exacerbated pulmonary inflammatory responses are the major causes of extensive diffuse alveolar immunopathological damage. However, the relationship between the extent of cytokine storm, neutrophils/macrophages infiltration, and different IAV infection dose and time still needs to be further elucidated, and it is still unclear whether the signal transduction and transcriptional activator 1/3 (STAT1/3) signalling pathway plays a beneficial or detrimental role. Here, we established a mouse model of high- and low-dose pH1N1 infection. We found that pH1N1 infection induced robust and early pathological damage and cytokine storm in an infection dose- and time-dependent manner. High-dose pH1N1 infection induced massive and sustained recruitment of neutrophils as well as a higher ratio of M1:M2, which may contribute to severe lung immunopathological damage. pH1N1 infection activated dose- and time-dependent STAT1 and STAT3. Inhibition of STAT1 and/or STAT3 aggravated low-dose pH1N1 infection, induced lung damage, and decreased survival rate. Appropriate activation of STAT1/3 provided survival benefits and pathological improvement during low-dose pH1N1 infection. These results demonstrate that high-dose pH1N1 infection induces robust and sustained neutrophil infiltration, imbalanced macrophage polarization, excessive and earlier cytokine storm, and STAT1/3 activation, which are associated with pulmonary dysregulated proinflammatory responses and progress of acute lung injury. The severe innate immune responses may be the threshold at which protective functions give way to immunopathology, and assessing the magnitude of host innate immune responses is necessary in adjunctive immunomodulatory therapy for alleviating influenza-induced pneumonia.